STRENGTHENING MENTAL HEALTH OF PARENTS THROUGH VIOLENCE PREVENTION EDUCATION PROGRAM - Nur Aisah Jamil; Nadya Yulianty S, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This educational program related to mental health aims to improve parents' mental health so that they have good psychological well-being and increase parents' understanding regarding the impact of violence on children's development. Parents who have good mental health will be happy individuals, have no symptoms of depression, have life satisfaction and are able to develop themselves well and also educate their children optimally so that children do not experience violence from their own parents. This educational program uses an educational and practical seminar approach to improve parents' mental health. The sample in this educational program was 25 parents in Cihanjawar Village, Bojong Purwakarta District. The research results showed that around 85% of parents participated in this educational program, parents felt calmer, more comfortable and relieved because in this mental health practice there was a release of negative emotions in the form of anger, annoyance, disappointment either due to conflicts with other people or while caring for their children. With educational programs related to mental health to prevent violence against children, this will positively improve parents' mental health so that parents can increase their self-awareness and control themselves in educating, caring for and guiding their children.